First record of one genus and two species of cockroach wasps (Hymenoptera: Apoidea: Ampulicidae: Dolichurinae) from Iran - Zahra Ghaderipour; M. Khayrandish; S. M. Madjdzadeh; Ebrahim Ebrahimi (نامه انجمن حشره‌شناسی ایران, 2020)
This paper provides a report on Dolichurinae (Hymenoptera: Ampulicidae) collected from different locations of southern Kerman province in southeast Iran from March to September 2017. In the present study, the genus Dolichurus latreille, 1809 (Hymenoptera: Ampulicidae: Dolichurinae) and two species, Dolichurus haemorrhous A. Costa, 1886 and D. corniculus Spinola, 1808 are recorded from Iran for the first time. Morphological remarks and illustrations of the newly recorded species are provided.